2009
DOI: 10.1111/j.1365-2133.2008.08887.x
|View full text |Cite
|
Sign up to set email alerts
|

RASandRAFmutations in banal melanocytic aggregates contiguous with primary cutaneous melanoma: clues to melanomagenesis

Abstract: Our findings hint towards the interpretation of banal melanocytic aggregates serving as precursor lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
1
37
1
1
Order By: Relevance
“…21 It has been previously pointed out that although activating mutations coexist, they are mutually exclusive at the single-cell level. 22 In the current study, intratumoral heterogeneity was seen only in one case, whereas intertumoral heterogeneity in the same patient (comparison of immunohistochemistry for NRAS mutational status of primary vs paired metastatic samples) was not an aim of the current study and future investigations will assess concordance of NRAS protein expression in multiple patient's tumors. Previous immunohistochemical analyses using BRAFV600E antibody have shown that intratumoral heterogeneity of BRAF mutation is not generally observed [23][24][25] and up to 100% concordance between matched primary and metastatic melanomas has been reported.…”
Section: Discussionmentioning
confidence: 71%
“…21 It has been previously pointed out that although activating mutations coexist, they are mutually exclusive at the single-cell level. 22 In the current study, intratumoral heterogeneity was seen only in one case, whereas intertumoral heterogeneity in the same patient (comparison of immunohistochemistry for NRAS mutational status of primary vs paired metastatic samples) was not an aim of the current study and future investigations will assess concordance of NRAS protein expression in multiple patient's tumors. Previous immunohistochemical analyses using BRAFV600E antibody have shown that intratumoral heterogeneity of BRAF mutation is not generally observed [23][24][25] and up to 100% concordance between matched primary and metastatic melanomas has been reported.…”
Section: Discussionmentioning
confidence: 71%
“…11 Our own previous experience has shown that the frequency could be even lower. 8 In spite of the low incidence rate, findings from this preliminary study shed light on the potential use of immunohistochemistry with the anti-B-Raf (V600E) antibody as an ancillary screening tool to assess the BRAFV600E mutation status in primary cutaneous melanoma. Further, in support of the specificity of this antibody, two cases in our cohort possessed mutations other than V600E (case 2 had a glutamic acid to lysine substitution while case 8 had a glutamic acid to methionine substitution) and were negative by immunohistochemistry (Figure 2).…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3] The BRAFV600E mutation is seen at particularly high rates in primary and metastatic melanoma (20-70%), papillary thyroid carcinoma (40-70%), colorectal carcinoma (5-10%), and in select benign tumors such as melanocytic nevi. 2,[4][5][6][7][8][9][10] Given its prevalence and role in increasing tumor cell proliferation and metastases, BRAFV600E has emerged as an important biomarker for clinicians. In early melanomas, the BRAF mutation status has not been shown to affect overall survival; however, in metastatic melanoma, it has been associated with a poorer survival rate.…”
mentioning
confidence: 99%
“…It is widely believed that a substantial percentage of melanomas arise from melanocytic nevi (Mooi and Krausz 2007). Indeed, several groups have provided genetic evidence that supports a progression model (Demunter et al 2001;Bogdan et al 2003;Yazdi et al 2003;Dadzie et al 2009). From the model outlined above, we and others deduced previously that abrogation of OIS of nevus cells may act as a rate-limiting event for melanomagenesis (Bennett 2003;Mooi and Peeper 2006).…”
mentioning
confidence: 99%